Los científicos en la organización y la gestión de la universidad: una visión histórica. - Villanueva Valdés, Miguel A.; González Redondo, Francisco A. (Revista Complutense de Educación, 2006)
The models of University organization and management can be studied from very different and complementary points of view. In this article the participation of two eminent scientists are studied, namely Blas Cabrera's (Rector) and Juan Negrín's (Secretary of the Faculty of Medicine) contributions at Madrid's Central University General Council at the beginning of the thirties. The analysis fulfilled, of an essential historical character, is based upon unpublished documents, namely the Council's Libro de Actas, whose first meeting took place on the 6th of March of 1930. As a whole, the study will aloud the detection of the various approaches to University organization and management. We will show those difficulties an experimental physicist as Blas Cabrera will suffer as Rector, opposite to the impressive qualities as organiser that can be seen in a physician and politician as Juan Negrín, whom, through his role should be considered undoubtedly the Council's alma mater.